How to Answer to the Challenges of Competencies Management in Collaborative Product Design? - Rose, B.; Robin, V.; Sperandio, S. (Cranfield University Press, 2009)
Collaboration is an essential factor of the design activities performance. This collaboration occurs between actors suited with varied expertises, coming from various trades and thus building a real network around the design project. It is advisable to manage with effectiveness the follow-up and the capitalization of information exchanged within this network. With the aim of increasing the performance of the design activity, the set up of competence management tools within the design teams is today necessary. However, these competencies management within a framework of collaborative design must answer various challenges. This article presents various proposals to answer them.
Organised by: Cranfield University
Keywords: Collaborative Design; Dynamic Competencies Management; Design Process Management